2006
DOI: 10.1590/s1519-69842006000100022
|View full text |Cite
|
Sign up to set email alerts
|

Considerations on the effect of anti-sandfly antibodies on biological parameters of Lutzomyia longipalpis (Lutz & Neiva, 1912) (Diptera: Psychodidae: Phlebotominae)

Abstract: ABSTRACTthe immunization of vertebrate hosts with vector components may be an alternative for the control of diseases transmitted by insects. in the present study we evaluated the effects of anti-sandfly antibodies on some of the biological parameters of female Lutzomyia longipalpis, a vector of visceral leishmaniasis. rabbits were immunized with extracts of gut from blood-fed (gb) or sugar-fed (gs) females, carcass of sugar-fed (Cs) or blood-fed (Cb) females, and with repeated sandfly bites (bite). immune ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Similarly, the percentage of engorgement in females of P. argentipes feeding on hamsters immunized by bites, gradually decreased ( Ghosh and Mukhopadhyay, 1998 ). However, no differences were observed in relation to the success of first feeding among the groups fed on animals immunized with different extracts or bite and the controls ( Vilela et al, 2006 ). Anti-saliva antibodies bind to the respective region of the antigen-presenting areas of the salivary gland.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, the percentage of engorgement in females of P. argentipes feeding on hamsters immunized by bites, gradually decreased ( Ghosh and Mukhopadhyay, 1998 ). However, no differences were observed in relation to the success of first feeding among the groups fed on animals immunized with different extracts or bite and the controls ( Vilela et al, 2006 ). Anti-saliva antibodies bind to the respective region of the antigen-presenting areas of the salivary gland.…”
Section: Discussionmentioning
confidence: 95%
“…In our experiments, hamsters were exposed to about 100-290 P. argentipes females six times at 7-15-day intervals, and antibody titres were very high compared to the control group. In L. longipalpis, Vilela et al [12] reported that females fed on animals immunized by repeated bites obtained lesser amounts of haemoglobin, laid fewer eggs and had higher mortality than females fed on naive animals [12]. On the contrary, Tripet et al [14] showed that egg production by L. longipalpis is not affected by feeding on immunized hosts, and studies on P. duboscqi and P. perniciosus also did not observe any differences in oviposition or mortality between experimental and control groups of sand flies [13,15].…”
Section: Discussionmentioning
confidence: 99%
“…In repeatedly-bitten hosts, sand fly saliva also stimulates the production of high levels of species-specific antisaliva antibodies [1]. According to some authors, these antibodies could have an impact on sand fly fecundity and mortality [10][11][12]; however, other studies have not found any significant effects [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Using a different approach, in the study conducted by Vilela and colleagues, rabbits were immunized through repeated sandfly bites and L. longipalpis females fed directly on these vaccinated animals. The authors observed a decline in the fecundity of these sandflies, in addition to the increased mortality of females [73]. In that same year, Saraiva et al conducted a study to evaluate the performance of the Leishmune ® vaccine as TBV in dogs.…”
Section: Development Of Tbvs For the Control Of Leishmaniasismentioning
confidence: 99%